PENGARUH JENIS SUSU PADA PH, TOTAL ASAM DAN WARNA KEFIR TRADISIONAL - Triana, Arli Nindi; Setyawardani, Triana; Sumarmono, Juni (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The aim of the study was to determine the effect of the type of milk on pH, total acid and color of traditional kefir. Materials and methods. The research materials used were 2 liters of pasteurized fresh cow's milk, 2 liters of pasteurized goat's milk, 2 liters of a combination of cow's milk and goat's milk (1:1 ratio), 2 liters of full fat commercial milk, 2 liters of low fat commercial milk, kefir seed starter. 150 grams, NaOH and phenolphthalein indicator. The research design used a completely randomized design (CRD) with 5 treatments and 4 replications. The treatments in this study included pasteurized fresh cow's milk (P1), pasteurized fresh goat's milk (P2), 1:1 combination of cow's milk and goat's milk (P3), full fat commercial milk (P4), low fat commercial milk (P5). ) with the addition of a 5% v/v kefir seed starter and an incubation period of 24 hours at room temperature. Results. The results of the analysis of variance showed that there was a very significant effect (P<0.01) on the pH value, total acidity and color of traditional kefir. The average pH value of kefir ranges from 4.1±0.1 to 4.8±0.2; total acid 0.8±0.1% to 2.0±0.1; color 65.7±2.0 to 80.2±4.2. Conclusion. The results can be concluded that Traditional kefir can be produced using various types of milk with the starter culture of kefir seeds resulting in varying pH, total acid and color, so the use of various types of milk as the basic ingredient for traditional kefir production affects product yields.